Treatment of striae albae with 1,550 nm Er: Glass vs. CO2 fractional laser: A self-controlled study - Luo, Yanfei; Lin, Yan; Wang, Meiling; Gao, Xiaoyuan; Liu, Xiaodong; Liu, Huaxu (Frontiers in Medicine, 2023)
Objective: To compare the efficacy and safety of fractional CO2 laser and 1550 nm Er : glass laser in the treatment of the patients with striae albae. Methods: The female adults with striae albae in the abdomen for at least 12 months were recruited. After informed consent obtained, the patient received three treatments at two-month intervals.The lesions on the left abdomen were treated with 10600 nm CO2 fractional laser and right side treated with 1550 nm Er : glass fractional laser. The pictures were taken before each visit and three months after the final treatment. The criteria for evaluations using a quartile grading scale were excellent (76-100%), good(51–75%), fair (26–50%), poor (1−25%)and no improvement (0%). The safety and efficacy of the two lasers were independently evaluated using before and after photographs by two dermatologists. And the self-reports to investigate the pain and satisfaction from patients were also recorded. Results: Totally 27 cases were recruited, and 25 patients completed the treatments and follow-up. The excellent and good results(improvement of 51%～100% ) were achieved on the right abdomen in 84% patients，while 48% on the left site ( P < 0.05) . Hyper-pigmentation was seen in 20% of the patients assessed on the left abdomen and only in 8% on the right abdomen. During the treatments，average score of the pain on the right abdomen was 5.41±2.13，which was higher than that on the left (4.19±2.12) ( P < 0.001 ). No permanent hyper- pigmentation was found on the both sides．And considering the whole treatments, the patients favored the modality used on the right side ( 80% versus 68%, P < 0.05) . Conclusion:Compared with CO2 fractional Laser, 1550 nm Er glass fractional laser therapy provides significantly better clinical outcomes and fewer side-effects in the treatment of striae albae. .Limitations: The sample size and follow-up time were limited.